Pengaruh Profitabilitas, Likuiditas, Ukuran Perusahaan, Dan Corporate Social Responsibility Terhadap Nilai Perusahaan - David Holyfil, Agustin Ekadjaja (Fakultas Ekonomi, Universitas Tarumanagara, 2021)
The purpose of this study was to analyze the effect of profitability, liquidity, firm size and corporate social responsibility on firm value on manufacturing companies listed on the Indonesia Stock Exchange in 2016-2018. This study uses 70 manufacturing companies that have been selected through a purposive sampling method with a total of 210 data for three years. The data used are secondary data in the form of financial statements which ends on 31 December ended period. Procesing data in this study using software Eviews version 10.0. The results of the study shows that profiability have a negative effect on firm value. Nonetheless, liquidity, firm size, and corporate social responsibility doesn’t have any impact on firm value.